Strategi Konten Dakwah Media Sosial - Alfajri, Faradis Zahra (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2022)
This study aims to find out what the strategy of Xkwavers is like in delivering da'wah through social media content on K-popers. The study used descriptive qualitative methods by obtaining data through interviews and content observations on the subjects studied. The theory used in this study is a communication strategy written by Hafied Cangara in his book Planning and Communication Strategy. This thought was adopted from what Harold Laswell said. Next there is medium theory and hypodermic syringe theory. The startegi da'wah conducted by Xkwavers is a sentimental da'wah startegi, startegi da'wah, rational and startegi indrawi da'wah from Albayanuni. The conclusion of the research is that da'wah can be done according to the jamanya. The use of social media is quite effectively used today, plus the existence of communication strategies and da'wah strategies used for the delivery of da'wah. Keywords : Albayanuni Dakwah Strategic; Social Media; Content; Strategic